2010
DOI: 10.1007/s00259-010-1621-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimal left ventricular lead position assessed with phase analysis on gated myocardial perfusion SPECT

Abstract: PurposeThe aim of the current study was to evaluate the relationship between the site of latest mechanical activation as assessed with gated myocardial perfusion SPECT (GMPS), left ventricular (LV) lead position and response to cardiac resynchronization therapy (CRT).MethodsThe patient population consisted of consecutive patients with advanced heart failure in whom CRT was currently indicated. Before implantation, 2-D echocardiography and GMPS were performed. The echocardiography was performed to assess LV end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 27 publications
2
64
1
2
Order By: Relevance
“…In a retrospective study conducted by Boogers et al, 13 All patients had a QRS ≥120 ms. They found that, compared with nonresponders, responders showed lower LVESV, LV dyssynchrony and myocardial scar burden.…”
Section: Spect Mpimentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study conducted by Boogers et al, 13 All patients had a QRS ≥120 ms. They found that, compared with nonresponders, responders showed lower LVESV, LV dyssynchrony and myocardial scar burden.…”
Section: Spect Mpimentioning
confidence: 99%
“…[8][9] Several myocardial imaging techniques have been developed to identify this position, such as echocardiography, [10][11] cardiac magnetic resonance imaging (CMR) 12 and nuclear imaging. [13][14][15] Placing the LV lead in the recommended position through coronary veins is a challenge. 16,17 This procedure requires high accuracy, since a difference of 20 mm in LV lead location on the myocardial wall can influence CRT response, and an incorrect LV lead pacing site may lead to greater myocardial dyssynchrony.…”
mentioning
confidence: 99%
“…There was no association between lead position in viable myocardium and persistent dyssynchrony by echocardiography, but pacemaker leads in all CRT responders were positioned in viable areas. A study in 90 HF patients with SyncTool [59] demonstrated that patients with lead placement concordant with the site of latest mechanical activation had a significantly higher response rate (n = 90, concordant: RSP = 79 %; discordant: RSP = 26 %), exhibiting significant LV systolic function improvement (assessed by echocardiography) at 6-month follow-up, while patients with discordant lead placement showed no significant improvement. To properly account for these factors, a comprehensive approach to CRT patient selection may be needed that combines phase analysis and myocardial scar evaluation, the latter both to assess overall scar burden and to evaluate myocardial viability at possible pacing sites.…”
Section: Crt and Patient Selection Optimizationmentioning
confidence: 99%
“…There is now a growing literature on the uses of MPS in cardiac failure. In addition to providing information on perfusion, it can give an accurate assessment of both systolic and diastolic left ventricular function, including phase and movement asynchrony which, in conjunction with CT anatomy information from hybrid imaging, can be used in planning for positioning of various intracardiac devices [22][23][24][25]. Another potential growth area in nuclear cardiac imaging is SPECT blood pool imaging.…”
Section: Software Developmentsmentioning
confidence: 99%